Chronic Cheek and Tongue Biting in Tourette Syndrome: A Case Report and Short Review - Najla Nadiah; Aura Sabita Rabbani; Rahmi Amtha; Adrianus Surya Wira Rajasa; Hrishikesh Sathyamoorthy (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2025)
Introduction: Tourette syndrome (TS) is a common neurodevelopmental disorder characterized by motor and vocal tics, often accompanied by neurobehavioral and psychiatric comorbidities such as anxiety and depression. Morsicatio buccarum (chronic cheek biting) and morsicatio linguarum (chronic tongue biting) are oral mucosal lesions primarily caused by recurrent self-inflicted trauma, frequently associated with psychological factors like anxiety or stress. While self-harming behaviors, including tongue and cheek biting, are observed in TS patients, the specific manifestation of morsicatio buccarum and linguarum as an associated feature in TS remains under-documented. This case report aims to highlight a compelling connection between morsicatio buccarum and linguarum and Tourette syndrome, particularly in the context of stress and anxiety, which can exacerbate both tics and oral parafunctional habits. Case: A 22-year-old male with a diagnosed history of Tourette syndrome presented with white linear elevations on the bilateral buccal mucosa and rough surfaces on the lateral borders of the bilateral tongue, which he had been aware of since elementary school. Intraoral examination confirmed diagnoses of morsicatio buccarum and morsicatio linguarum. Case Management: The Depression, Anxiety, and Stress Scale (DASS-21) questionnaire was administered to assess psychological factors, which indicated severe depression and anxiety, and moderate stress. The patient received comprehensive communication, instruction, and education regarding his conditions. Conclusion: This case suggests that morsicatio buccarum and linguarum can be a behavioral manifestation or co-occurring condition.